Lithuanian Fairy Tale “Bearskin” (ATU 361): European Context and Local Peculiarities - Šlekonytė, Jūratė (Tautosakos darbai, 2024)
The subject of this article is a popular Lithuanian fairy tale “Bearskin” (ATU 361), evolving around an unusual contract between a man and the devil. The man is obliged to neglect his bodily hygiene during a certain number of years (i. e. not wash himself nor cut his hair, nor shave). After fulfilling this request, he receives a material award and a bride of high social standing. The article attempts establishing the reasons for the devil to make this request regarding neglect of the bodily hygiene during the time of the service. Since the fairy tale is widespread across Europe, the author briefly presents its international variants as well. The study embraces more than just the Lithuanian material, therefore the origins of the certain fairy tale images are established with regard to the other nations’ customs and beliefs, along the Lithuanian ones. The analysis of the tale allows concluding that the period of bodily impurity could be interpreted as a time of separation, of inclusion of the hero into unhuman world, during which he becomes closer to the otherworldly forces. Afterwards, a symbolic rebirth and change of the social status follow. This is related to the male maturity, and the man’s passage into another social stage, i. e. marriage. In order to reach a higher social step, the man has to undergo symbolical purification. Besides, the image of the dirty man might send a message regarding the strange and reclusive people who stand out among others due to their repulsive appearance and unusual behaviour. Analysis of this tale revealed yet another important side of its development, namely, the likely impact of the published variants onto the oral tradition. Already in the first half of the 19th century, the Grimm Brothers published the variant of the tale (KHM nr. 101) that received broad popularity and could have affected other international variants. This German variant, most likely, affected also the Lithuanian tales about the human contract with the devil. The Grimms’ tale “Bearskin” was first published in Lithuanian in 1926 and reprinted several times afterwards. According to the analysis, at least four Lithuanian variants of this tale display elements of the Grimms’ tale, or even present rather detailed renderings of the German tale’s plot.